Sign2Sign - A First Attempt - Weng, Titus; Lee, SingChun (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR); 2024: Anais Estendidos do XXVI Simpósio de Realidade Virtual e AumentadaDO - 10.5753/svr_estendido.2024.244070, 2024)
At the core of human engagement is communication. While technological advances enable convenient translation for different language speakers to communicate, millions of Deaf, Mute, and Hard-of-Hearing people still face immense hurdles due to the lack of accessible tools to facilitate direct sign language translation. Our project aims to build a Sign2Sign direct immersive translation tool using WebXR that takes input from any accessible camera and produces output in WebXR-supported platforms. This paper presents the preliminary results of direct translation between ten gestures of American and Chinese Sign Languages for sign language translations in an immersive environment.